2016
DOI: 10.1159/000445894
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Surface Antigen Variants of Hepatitis B Virus in Tunisian Patients

Abstract: In Tunisia, the prevalence of naturally occurring surface (S) gene variants of hepatitis B virus (HBV) has not been determined. In the present study, the prevalence of these variants was examined in terms of the clinical and viral state in a series of 99 Tunisian patients with HBV infection. The S genes were amplified and directly sequenced. Genotype D was predominant (98%), 40.4% isolates belonged to subgenotypes D7 and 1 to subgenotype D2. The most common subtype was ayw2 (95.9%). In total, 60.6% of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The efficacy of mass vaccination programmes has been confirmed in other settings such as in The Gambia, where the prevalence of chronic hepatitis B was reduced from 12.4% to 0.8% [94,95,96]. In Tunisia, the universal immunisation programme has resulted in 68.9% of those immunised carrying the protection of levels of anti-HBs >10 mIU/mL into early adulthood [97], whereas a vaccine programme at 6, 10, and 14 weeks has resulted in sero-protection in 87% of immunised infants in South Africa [98]. Data from Taiwan importantly demonstrates the efficacy of a universal immunisation programme in reducing the longer-term risk of HCC [99].…”
Section: Hbv Vaccine and Prospects For Hbv Eliminationmentioning
confidence: 99%
“…The efficacy of mass vaccination programmes has been confirmed in other settings such as in The Gambia, where the prevalence of chronic hepatitis B was reduced from 12.4% to 0.8% [94,95,96]. In Tunisia, the universal immunisation programme has resulted in 68.9% of those immunised carrying the protection of levels of anti-HBs >10 mIU/mL into early adulthood [97], whereas a vaccine programme at 6, 10, and 14 weeks has resulted in sero-protection in 87% of immunised infants in South Africa [98]. Data from Taiwan importantly demonstrates the efficacy of a universal immunisation programme in reducing the longer-term risk of HCC [99].…”
Section: Hbv Vaccine and Prospects For Hbv Eliminationmentioning
confidence: 99%
“…Recent studies reported predominance of genotype D (over 80%) with limited circulation of genotypes A, B, C, and E [Meldal et al, 2009;Hannachi et al, 2010;Ezzikouri et al, 2013]. HBV-D7 has been reported as one of the dominant subgenotype circulating in Tunisia [Meldal et al, 2009;Hannachi et al, 2010;Chaouch et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the amino acid sequences of the 9736409 open reading frames (ORFs) did not identify escape or resistance mutations in HBsAg or the polymerase. However, an early stop codon was identified in the HBsAg ORF at amino acid position 216 (T801A), which is a naturally occurring variant that results in a 10–amino‐acid truncation of the HBsAg ORF . While our direct amplicon sequencing method identified this variant as the major sequence present in 9736409, the possibility cannot be ruled out that a minor population of wildtype virus could produce full length HBsAg in this specimen.…”
Section: Discussionmentioning
confidence: 93%
“…However, an early stop codon was identified in the HBsAg ORF at amino acid position 216 (T801A), which is a naturally occurring variant that results in a 10-amino-acid truncation of the HBsAg ORF. 30 While our direct amplicon sequencing method identified this variant as the major sequence present in 9736409, the possibility cannot be ruled out that a minor population of wildtype virus could produce full length HBsAg in this specimen. In a comparison of all 39 HBV-I genomes with HBsAg and pre-C coverage, only one other strain (LA.KF214679, G668A) carried a nonsense HBsAg mutation, although it is unknown whether HBsAg was detectable in this specimen.…”
Section: Examination Of the Amino Acid Sequences Of The 9736409 Openmentioning
confidence: 86%